Transport and Pre-hospital Care Prior to Arrival in Tertiary Care Emergency Department of Eastern Nepal: a Cross sectional Study - Giri, Sonai Chaudhuri; Malla, G; Bhandari, R; Poudel, M; Giri, S (Journal of BP Koirala Institute of Health Sciences, 2019)
Introduction: Nepal has diverse terrain and the length of time taken by the patients to get medical help is often too long. Road linkage transport may not exist, inadequate or are unreliable and irregular. Materials and Methods: After ethical clearance, this prospective observational study was done by convenient sampling, among 2211 patients arriving in the emergency ward of B. P. Koirala Institute of health science over a period of one month. A pre-tested validated questionnaire consisting of questions related to study objectives (i.e. demography, preferred mode of transport, reasons for choosing the transport, facilities available in ambulance, cost and time taken through ambulance service and any pre-hospital care received) was handed over to the patient or their relatives and their responses were collected. Descriptive analysis was done in SPSS software version 11.2. Result: Out of the 2211 patients presented in emergency ward, 43.2% (955) came in an ambulance. Patients with ATS 2 (very sick) arriving in ambulance were 27.6%. The median time taken by ambulance is 2 hours (IQR 1-3hrs). The median distance covered is 55km ((IQR 38km- 80km). The median cost paid was USD 31.25 or NRs. 3500 (IQR NRs 2000- NRs 6000, USD 17.86- 53.57).Their main reason expressed for not choosing ambulance service was high cost, i.e. expensive (26%).About one third subjects (29.4%) had used some sort of pre-hospital care. Conclusion: Patients preferred private vehicles to arrive in emergency ward of this hospital with high acuity triage score (ATS 2). Awareness needs to be raised among Nepalese population to enhance the practice of using ambulance service for patient transport.